Las facultades legales del servicio nacional de aduanas en materia de adjudicación gratuita en la normativa ecuatoriana. - Granda Balcazar, Josselyn Katherine (My University, 2018)
In this paper we study the legal powers of the National Customs Service of Ecuador (hereinafter SENAE), as the competent authority in the matter of free adjudication of certain goods. The general objective was to analyze this faculty to benefit non-profit organizations and the process they must follow to benefit from the free delivery of certain merchandise. The research was based on the application of a qualitative methodology, through a documentary analysis approach on legal regulations and scientific articles. This implied the revision of the Organic Code of Production, Commerce and Investments and the Regulation of Book V and more than 10 papers. According to the results obtained, it was concluded that this is a highly regulated administrative procedure aimed at promoting the country's social policy. Pursues that merchandise abandoned in customs can be used or benefited by other individuals outside the State, but for social and economic purposes relevant to national needs.
En este trabajo estudiamos las facultades legales que tiene el Servicio Nacional de Aduanas del Ecuador (en adelante SENAE), como autoridad competente en materia de adjudicación gratuita sobre determinadas mercancías. El objetivo general fue analizar dicha facultad para beneficiar a las organizaciones sin fines de lucro y el trámite que estas deben seguir para verse beneficiado de la entrega gratuita de ciertas mercancías. La investigación se basó en la aplicación de una metodología cualitativa, mediante un enfoque de análisis documental sobre la normativa legal y artículos científicos. Esto implicó la revisión del Código Orgánico de Producción, Comercio e Inversiones y el Reglamento del Libro V y más de 10 papers. De acuerdo a los resultados obtenidos, se concluyó que se trata de un procedimiento administrativo muy reglado y orientado al fomento de la política social del país. Persigue que las mercancías abandonadas en aduanas puedan ser aprovechadas o beneficiadas por otras personas particulares ajenas al Estado, pero con fines sociales y económicos relevantes para las necesidades nacionales.
Keywords: AUTORIDAD ADUANERA; DESTINOS ADUANEROS; ABANDONO DE MERCANCÍA; ADJUDICACIÓN GRATUITA